Hydrophilic sputtered AR coating
By adopting a multi -layered coating system on the ophthalmology lens, including alternate low refractive index and high refractive index layers, a high refractive index layer is encapsulated between the low refractive silicon layer, which solves The existing hydrophilic coating is the problem of insufficient durability of the coating, and it has achieved long -term easy cleaning and anti -reflexivity.
Patent Information
- Application Number
- CN202080064124.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-07-12
- Filing Date
- 2020-07-13
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2040-07-13
AI Technical Summary
The existing hydrophilic coatings tend to lose durability after long-term use, and cannot effectively maintain the easy cleaning and anti-reflective properties of the ophthalmic lens surface.
The coating system with a multi -layer structure, including alternate low refractive rate layers and high refractive index layers, low refractive index layers contain silicon dioxide, high refractive index layer contain titanium dioxide or dioxide, and metal oxide nitride, through DC The pulse sputtering technology deposition these layers to ensure that a high refractive index layer of the oxygen nitrogen is encapsulated between the low refractive silicon layer.
The long-term remained easy to clean and anti-reflexivity of the surface of the ophthalmical products. Surface freedom can maintain nearly 40 days within the range of about 50-70mn/m. The cleaning rate is better than 90%, which significantly improves the durability of the coating.
Smart Images

Figure CN114364528B_ABST
Abstract
Description
[0001] Related Applications
[0002] This application claims the benefit of U.S. Provisional Application Serial No. 62 / 873,779, filed on July 12, 2019, entitled HYDROPHILIC SPUTTERED AR COATINGS, which is hereby incorporated by reference in its entirety. Technical Field
[0003] The present invention relates to optical coatings, and more particularly to easy to clean and anti-reflective hydrophilic sputtered coatings. Background Art
[0004] One or more functional coatings may be applied to the surface of an ophthalmic article to impart different properties or characteristics to the surface. These properties or characteristics imparted by the coating may include color, gloss, reflectivity, wear resistance, optical clarity, water resistance, fog resistance, anti-reflection, stain resistance, and ease of cleaning. Among these different properties, the surface properties or characteristics of easy cleaning and anti-reflection have potential for widespread application in the ophthalmic industry.
[0005] Dirt, oil and dust are the main contaminants of ophthalmic lenses. Removal of these contaminants is ongoing and often challenging depending on the wearer's environment, the type of ophthalmic lens coating and the materials required to clean the ophthalmic lens coating.
[0006] In order to keep the surface of ophthalmic lenses clean, many manufacturers use hydrophobic coatings on these lenses and market the hydrophobic coatings as being smoother or more hydrophobic on their surfaces than competing glasses and therefore easier to clean. However, market research has shown that these easy-to-clean coating technologies that use hydrophobic or smooth lens surfaces have not performed to the expected level for a number of reasons.
[0007] The first reason is that a hydrophobic or slippery surface does not necessarily mean that oil and stains will generally fall off or be easily removed. Instead, oil and stains tend to move around more easily on the surface, and in the absence of friction from the surface, oil and stains tend to smear across the lens surface.
[0008] The second reason is that existing easy-to-clean coating technologies using hydrophobic surfaces are primarily concerned with achieving the maximum possible contact angles for water and oil. The reason for these large contact angles is the correlation between the maximum contact angles for water and oil and the resistance of the surface to stains, fingerprints, and ease of cleaning. In general, contact angles for water of >110° before rubbing and >105° after rubbing are commonly used. However, a large contact angle does not necessarily always indicate an easy-to-clean surface, as a mixture of oil and stains tends to migrate or smear on a smooth lens surface.
[0009] The third reason is that the hydrophobic surface properties may not be maintained over time. During the lens cleaning process, the hydrophobic coating can deteriorate or wear away over time. When this happens, oil and stains accumulate on the lens and are difficult to remove without the use of soap or similar cleaning solutions.
[0010] Typically, these hydrophobic coatings rely on the photocatalytic activity of the coating, a property most commonly seen in titanium dioxide (titania or titanium oxide, TiO2) coatings. As a broadband semiconductor, TiO2 absorbs light in the UV wavelength. The absorption process produces electron-hole pairs and photogenerated holes, which are responsible for the hydrophilicity of the coating surface (water contact angle less than 10°). The capture of pollutants like water or oil by holes leads to the formation of charged species, such as hydroxyl ions and hydroxyl radicals, by oxidation. These charged species can have several effects: a) charged species can create hydrophilicity on the surface (through surface recombination if TiO2 increases the density of hydroxyl radicals on the surface); b) charged species can provide a self-cleaning mechanism through oxidation of surface pollutants; and c) photocatalytic action that converts pollutants into non-hazardous materials.
[0011] The photocatalytic effect of TiO2 coatings is the subject of many patents (including US2003 / 0048538A1, US7527867, US5854708 and US 6830785), the contents of which are hereby incorporated by reference. In these patents, the photocatalytic properties of TiO2 are used to provide increased hydrophilicity (water contact angle less than 10°) and, in some cases, provide a self-cleaning mechanism that helps maintain the hydrophilicity when the surface becomes dirty.
[0012] In some cases, silicon dioxide (SiO2) is added to the photocatalytic TiO2 as a dopant, as seen in US 6830785, or as a layer on top of TiO2, as seen in US 2003 / 0048538A1, the contents of which are hereby incorporated by reference in their entirety, to improve the hydrophilic behavior of the coated TiO2. And the use of titanium oxynitride (TiO2) is discussed in the publication of Asahi [“Visible Light Photocatalyst in Nitrogen Doped Titanium Oxides”, Asahi, Morikawa, Ohwaki, Aoki, Taga, Science 293 pg. 269]. x N y) as a photocatalyst, the contents of which are incorporated herein by reference in their entirety. By adding nitrogen, the band gap of the semiconductor is narrowed, allowing the absorption of high-energy visible light to generate electron-hole pairs. When exposed to UV radiation, the photocatalytic behavior of TiOxNy is similar to that of TiO2. However, with TiO x N y The observed photocatalytic effect (under UV or visible light illumination) is much weaker than that of TiO2 under UV illumination. x N y As a photocatalytic material, it is not as efficient as TiO2 in converting photons into the desired change in surface energy or reactivity.
[0013] However, these types of hydrophilic coatings are generally not durable over extended periods of time and cannot be used in applications where abrasion is present. Furthermore, in these types of hydrophilic coatings, the surface energy of the ophthalmic surface decreases over time and eventually approaches zero, so the hydrophilic coating no longer provides a favorable surface energy to promote the easy-cleaning properties of the ophthalmic lens.
[0014] Therefore, there is a need to develop coatings and coating systems that overcome the shortcomings of existing hydrophilic coatings by providing improved cleaning characteristics and improved durability over longer periods of time. Summary of the invention
[0015] The coatings and coating systems provided by the present invention impart effective easy-clean properties to the surfaces of ophthalmic articles. According to some embodiments, the coating system of the ophthalmic article is achieved by providing a substrate having a surface and a plurality of alternating low refractive index layers and high refractive index layers, wherein the low refractive index layers comprise metal oxides including silicon dioxide. The alternating high refractive index layers comprise a second metal oxide comprising titanium dioxide or zirconium dioxide, and at least one metal oxynitride comprising titanium oxynitride or zirconium oxynitride, all of which are deposited on the surface of the substrate. In this coating arrangement, when the at least one high refractive index titanium oxynitride or zirconium oxynitride is encapsulated between two layers of silicon dioxide having a low refractive index, the ophthalmic article comprises a long-term surface free energy in the range of about 50-70 mN / m, for example, nearly 40 days.
[0016] According to some embodiments of the present invention, high index metal oxynitrides (titanium or zirconium) are engineered into improved anti-reflective optical stacks as hydrophilic surfaces to increase their cleanability or optical articles. This layer is preferably constructed within an anti-reflective (AR) optical stack, so that no additional layers outside the AR stack are required to make the optical article easier to clean. The metal oxynitride film, when used in combination and encapsulated between silicon dioxide, develops hydrophilic properties during the sputtering process of the thin film AR depending on the nitrogen to oxygen ratio.
[0017] In some embodiments of the present invention, a method for making an ophthalmic article having easy-to-clean and anti-reflective properties is described. The method includes providing a substrate having a first surface, and forming a plurality of alternating low-refractive index metal oxide layers and high-refractive index metal oxide layers and metal oxynitride layers on the first surface. The plurality of alternating layers also includes at least one high-refractive index metal oxynitride encapsulated between two layers of low-refractive index metal oxide. By encapsulating at least one high-refractive index metal oxynitride layer between two layers of low-refractive index metal oxide, the ophthalmic article is made to have easy-to-clean properties. The surface cleaning rate of the ophthalmic article in the coating system is preferably greater than 90%. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] These and other aspects, features and advantages of embodiments of the present invention are apparent from and will be elucidated from the following description of embodiments of the present invention, with reference to the accompanying drawings, in which:
[0019] Figure 1 is a perspective view of a coated substrate according to one embodiment of the present invention.
[0020] Figure 2 is a perspective view of a coated substrate according to another embodiment of the present invention.
[0021] Figure 3 is a table showing the differences in refractive index, thickness, and surface roughness between zirconium oxide and zirconium oxynitride.
[0022] Figure 4 is a combined graph showing the measured contact angles (water and diiodomethane) and the calculated surface energies (total, dispersive, and polar) on surfaces freshly coated with a silicon dioxide layer, freshly coated with silicon dioxide and zirconium oxynitride layers, and freshly coated with encapsulated zirconium oxynitride between two silicon dioxide layers.
[0023] Figure 5 is a combined graph showing the measured contact angles (water and diiodomethane) and the calculated surface energies (total, dispersive and polar) on a surface coated with Figure 4 The layer.
[0024] Figure 6 is a comparative graph showing the contact angle of water on a surface over time when coated with an AR coating containing SiO2 and titanium oxide or titanium oxynitride. In the stack design, the outermost layer is SiO2.
[0025] Figure 7 is a comparison graph showing the contact angle of water on a surface over time when coated with an AR stack containing SiO2 and either zirconium oxide or zirconium oxynitride. In the stack design, the outermost layer is SiO2.
[0026] Figure 8is a comparison graph showing the contact angle of diiodomethane over time on a surface coated with an AR coating containing SiO2 and either titanium oxide or titanium oxynitride. In the stack design, the outermost layer is SiO2.
[0027] Fig. 9 is a comparison graph showing the contact angle of diiodomethane over time on surfaces coated with SiO2 and AR coatings of zirconium oxide or zirconium oxynitride. In the stack design, the outermost layer is SiO2.
[0028] Fig.10 is a comparative graph showing the surface free energy of a surface as a function of time when coated with an AR coating containing SiO2 and either titanium dioxide or titanium oxynitride. In the stack design, the outermost layer is SiO2.
[0029] Fig.11 is a comparative graph showing the surface free energy of a surface as a function of time when coated with an AR coating containing SiO2 and zirconium oxide or zirconium oxynitride. In the stack design, the outermost layer is SiO2.
[0030] Fig.12 is a comparison graph showing the time-dependent free energy of the dispersion component of a surface when coated with an AR coating containing SiO2 and either titanium dioxide or titanium oxynitride. In the stack design, the outermost layer is SiO2.
[0031] Fig.13 is a comparative graph showing the time-varying free energy of the dispersion component of a surface when coated with an AR coating containing SiO2 and zirconium oxide or zirconium oxynitride. In the stack design, the outermost layer is SiO2.
[0032] Fig.14 is a comparison graph showing the free energy of the polar component of a surface as a function of time when coated with SiO2 and either titanium dioxide or titanium oxynitride. In the stack design, the outermost layer is SiO2.
[0033] Fig.15 is a comparison graph showing the free energy of the polar component of a surface as a function of time when coated with SiO2 and zirconium oxide or zirconium oxynitride. In the stack design, the outermost layer is SiO2.
[0034] Fig.16 is a comparison chart showing the cleanability ratios of zirconium oxide or zirconium oxynitride used as high refractive index layers in anti-reflection and easy-clean stacks. In the stack design, the outermost layer is SiO2.
[0035] Fig.17is a table showing a comparison of cleanability ratios between a competitor's hydrophobic coating, an easy-to-clean coating in earlier US Pat. No. US10613255B2, and the coating disclosed in the present invention (labeled "Hydrophilic AR"). DETAILED DESCRIPTION
[0036] Specific embodiments of the present invention will now be described with reference to the accompanying drawings. However, the present invention may be embodied in many different forms and should not be construed as being limited to the embodiments described herein; rather, these embodiments are provided to make the disclosure of the present invention thorough and complete and to fully convey the scope of the present invention to those skilled in the art. The terms used in the detailed description of the embodiments illustrated in the accompanying drawings are not intended to limit the present invention. In the drawings, like numbers refer to like elements.
[0037] The present invention provides a coating system for an ophthalmic article, comprising at least one high refractive index metal oxynitride coating. The presence of at least one layer of metal oxynitride in the anti-reflective optical stack of the ophthalmic article provides a favorable surface energy, making the surface hydrophilic, thereby enhancing the easy-to-clean properties of the surface of the ophthalmic article from stains, skin oils and dust. The easy-to-clean coating or layer of the present invention can be applied to ophthalmic articles, including but not limited to glass, plastic, metal, painted or colored surfaces, and other materials that need to be cleaned.
[0038] In some embodiments of the present invention, the easy-to-clean coating or layer includes at least one layer of high refractive index titanium oxynitride or zirconium oxynitride, which provides a continuously increased surface energy to the surface of the ophthalmic article. In some embodiments, the easy-to-clean and anti-reflective optical stack of the ophthalmic article includes at least one layer of titanium oxynitride or zirconium oxynitride, and a silicon dioxide layer. In some other embodiments, the easy-to-clean and anti-reflective optical stack of the ophthalmic article includes at least one layer of titanium oxynitride or zirconium oxynitride and a silicon dioxide layer and a titanium dioxide layer or a zirconium dioxide layer.
[0039] In some embodiments of the present invention, a process for preparing an anti-reflective stack with easy-to-clean properties comprises depositing at least one layer of high-refractive index titanium oxynitride or zirconium oxynitride into a low-refractive index silicon dioxide layer using DC pulse sputtering at 150Khz in a vacuum. In some embodiments, when at least one layer of high-refractive index titanium oxynitride or zirconium oxynitride is encapsulated between two layers of low-refractive index silicon dioxide in the optical stack, the easy-to-clean and anti-reflective optical stack surface of the ophthalmic article produces a controllable hydrophilic surface energy.
[0040] According to some embodiments, a non-limiting example of a standard anti-reflective and easy-to-clean stack design employs a five-layer structure of a L / H / L / H / L stack, where L is a low-refractive-index silicon dioxide layer and H is a high-refractive-index titanium oxynitride layer, zirconium oxynitride layer, titanium dioxide layer, or zirconium dioxide layer. In some embodiments, when at least one high-refractive-index layer includes a titanium oxynitride layer or a zirconium oxynitride layer, the ophthalmic article produces a durable, controllable hydrophilic surface energy.
[0041] In some embodiments of the present invention, the preparation of the titanium oxynitride layer or the zirconium oxynitride layer includes sputtering deposition from a titanium or zirconium metal target in the presence of oxygen and nitrogen to form the desired metal oxynitride layer. In some embodiments of the present invention, the preparation of the silicon dioxide low refractive index material includes sputtering deposition from a silicon target in the presence of oxygen to deposit silicon dioxide.
[0042] In some embodiments of the present invention, standard vivid 5 / 7CX / CC (CC-concave, CX-convex) and 99.98% pure zirconium were used as high refractive index metal for sputtering. In some embodiments, 99.999% pure silicon was used as low refractive index material for sputtering. In some other embodiments, 6% boron was doped into silicon as low refractive index material for all control tests.
[0043] In some embodiments of the present invention, at any given process flow, the sputtering gas includes argon, oxygen, and nitrogen. According to some embodiments, the mass flow controllers used in these processes are 50 sccm for both argon and oxygen flow rates. When nitrogen is used as the sputtering gas, a mass flow controller of 5 sccm is used instead of 50 sccm because a small flow of 3.5 sccm is required to coat the nitride. In some embodiments of the present invention, during testing, the adhesion layer of the silicon process was about 20-30 angstroms.
[0044] In some embodiments, the method for making metal oxynitride is carried out by DC pulsed magnetron sputtering in the metal mode using a reactive plasma tube (barrel). The sputtering system used in the present invention is detailed in U.S. Patent Application 2014 / 074912, the contents of which are incorporated herein by reference. During the sputtering process, the material is applied as a very thin metal and rotated by a reactive plasma. Due to the structure of the plasma source and the placement of the cathode, most types of gases can be delivered in the cathode or plasma tube. In some embodiments, an inert gas (e.g., argon) and a reactive gas (e.g., nitrogen) are delivered to the cathode, and another reactive gas (e.g., oxygen) is delivered to the plasma tube. In some embodiments, a mass flow controller of 2.5 to 3.5sccm is sufficient to obtain a metal oxynitride layer in a consistent process. In the present invention, all samples were prepared using a Mycoat DC pulsed sputtering system with a metal mode plasma tube for reacting a metal film to produce an oxide or oxynitride.
[0045] In the present invention, the anti-reflection color specification is used for testing, which is tracked from time zero and over a period of time. In addition, in the present invention, the hydrophilic anti-reflection process is used for some different types of lenses. Non-limiting examples of such lenses are polycarbonate Tegra and Clear Blue Filter, CR39, which have high refractive indices of 1.67 and 1.70 respectively. The original anti-reflection formula is adjusted in color and spectrum as needed to achieve specifications with little impact on surface energy and cleanability results.
[0046] In some embodiments of the present invention, the high refractive index layer of titanium oxynitride or zirconium oxynitride acts in three ways in the anti-reflection stack of the ophthalmic product. The first way is that the surface morphology changes during the growth of the titanium oxynitride or zirconium oxynitride film layer in the stack. In some embodiments, a 10nm thick titanium oxynitride or zirconium oxynitride film layer acts the same as a 100nm thick titanium oxynitride or zirconium oxynitride film layer in terms of surface energy and / or surface morphology. In some embodiments, a thin film layer of titanium oxynitride or zirconium oxynitride is placed in an anti-reflection optical stack to change the performance of the entire optical stack in terms of cleanability and surface free energy. According to some embodiments, a non-limiting example of a standard anti-reflection and easy-to-clean stack design uses a five-layer structure of a L / H / L / H / L stack, where L is a low refractive index silicon dioxide layer and H is a high refractive index at least a titanium oxynitride coating or a zirconium oxynitride coating. In this regard, a high refractive index refers to a refractive index greater than about 1.7 at a reference wavelength (e.g., a wavelength of about 550 nanometers). Low refractive index refers to a refractive index of less than about 1.5 at a reference wavelength (e.g., a wavelength of about 550 nanometers). The columnar growth of this L / H / L / H / L stack also increases the surface area, and the increase in surface area plays a role in achieving a controllable surface free energy (SFE), ultimately leading to improved easy-to-clean properties of the ophthalmic article. The columnar growth may also result in an increase in the coefficient of friction of the surface, thereby creating a "grabby feel" on the lens surface.
[0047] The second way in which the presence of the metal (Ti / Zr) oxynitride layer / multilayers affects the anti-reflection stack is by providing a controllable surface free energy of the total optical anti-reflection stack. In some embodiments, the presence of the metal (Ti / Zr) oxynitride layer / multilayers affects the anti-reflection stack by providing a controllable surface energy in the range of about 50-70 mn / m. In such embodiments, each layer of the metal (Ti / Zr) oxynitride layer / multilayers interacts with the other optical stack layers in the controlled surface energy in the range of about 50-70 mn / m and contributes to the overall surface free energy of the hydrophilic surface and the general cleanability of the surface.
[0048] The third way in which the presence of a metal (Ti / Zr) oxynitride layer / multilayers affects surface hydrophilicity is through the suspected photocatalytic properties of the titanium or zirconium oxynitride layer, which generates holes in the presence of sunlight (photons), thereby oxidizing surface water and oil through these holes to produce OH radicals.
[0049] Now refer to the present invention Figure 1 , which shows an embodiment in which a durable anti-reflective coating with easy-to-clean properties is provided on the surface of an article 10 (e.g., an optical lens). Figure 1In this embodiment, the coating system 20 includes a five-layer stack of alternating L / H / L / H / L layers, where L is a low refractive index silicon dioxide layer (20a, 20c, 20e), and H is a high refractive index layer (20b or 20d), at least one of which is composed of titanium oxynitride or zirconium oxynitride (20b or 20d). The other high refractive index layers can be titanium dioxide layers, zirconium dioxide layers, titanium oxynitride layers, or zirconium oxynitride layers. The pre-adjusted anti-reflective and easy-to-clean stack 20 can employ, for example, at least three layers of alternating high-index and low-index refractive layers, but the number of alternating layers is not necessarily limited (for example, the stack 20 can include 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16 or more layers). In this regard, the stack can have 20n layers, where n is equal to the number of layers present.
[0050] For example, the refractive layer 20n may include alternating layers of low refractive index silica and high refractive index titanium oxynitride. In another example, the refractive layer 20n may include alternating layers of low refractive index silica and 1) one or more high refractive index titanium oxynitride layers, and 2) one or more high refractive index titanium dioxide layers. In another example, the refractive layer 20n may include alternating layers of low refractive index silica and high refractive index zirconium oxynitride. In another example, the refractive layer 20n may include alternating layers of low refractive index silica and 1) one or more high refractive index zirconium oxynitride layers, and 2) one or more high refractive index zirconium dioxide layers. In all embodiments of the present invention, the easy-to-clean and anti-reflective optical stack of the ophthalmic product includes at least one layer of high refractive index titanium oxynitride or zirconium oxynitride, as well as a low refractive index silica layer and a high refractive index titanium dioxide layer or zirconium dioxide layer. In some embodiments, at least one layer of high refractive index titanium oxynitride or zirconium oxynitride ( Figure 1 , 20b or 20d) is encapsulated between two layers of low refractive index silicon dioxide (20a, 20c, 20e) within the stack.
[0051] Figure 2 An alternative example of an embodiment of the present invention is shown in which the coating system 20 includes a seven-layer stack of alternating L / H / L / H / L / L layers, where L is a low refractive index silicon dioxide layer (20a, 20c, 20e, 20g) and H is a high refractive index layer, where at least one high refractive index layer is a titanium oxynitride or zirconium oxynitride (20b or 20d or 20f) coating / layer. The other high refractive index layers can be titanium dioxide layers or zirconium dioxide layers. The pre-adjusted anti-reflection and easy-to-clean stack 20 can employ, for example, at least three layers of alternating high-index and low-index refractive layers, but the number of alternating layers is not necessarily limited (for example, the stack 20 can include 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16 or more layers). In this regard, the stack can have 20n layers, where n is equal to the number of layers present.
[0052] Reference now Figure 3 Table comparing the differences in refractive index, thickness, and surface roughness between zirconium oxynitride and high refractive index layers of zirconium oxynitride, measured using an ellipsometer. Thin films of zirconium oxynitride and zirconium dioxide were coated on fused quartz and measured. Silicon dioxide was normalized in the measurements. The data shows that there is very little difference in refractive index (e.g., a difference of 0.0032) and optical composition of the materials between the zirconium oxynitride and zirconium dioxide layers, but column 3 of the table shows that there is a difference in surface roughness (e.g., a difference of about 0.63 nm) between zirconium oxynitride and zirconium dioxide. The surface roughness of the high refractive index coating of zirconium oxynitride is 4.43 nm, which is higher than the surface roughness of the high refractive index coating of zirconium dioxide, which is 3.80 nm. Since an increase in surface roughness is generally associated with a more hydrophilic surface, the high refractive index coating of zirconium oxynitride with a surface roughness of 4.43 nm tends to be more hydrophilic than the high refractive index coating of zirconium dioxide with a surface roughness of 3.80 nm.
[0053] Figure 4 A graph showing the measured contact angles (in water and in diiodomethane) and the calculated surface free energies (total, dispersive, and polar) for a silica layer, a silica layer with zirconium oxynitride, and a zirconium oxynitride layer encapsulated between silica layers. Note that the date 8 / 1 / 18 refers to the sample creation date (i.e., time zero measurement). Figure 4 In this paper, anti-reflective, easy-to-clean stacks consisting of monolayers of high- and low-refractive-index materials of different thicknesses were measured with a goniometer for contact angles (in water and diiodomethane) and total surface free energy (total, dispersive and polar). The experiments showed that the contact angle and total surface free energy vary depending on the order of the multilayers and the individual layers. In this paper, the total surface free energy is composed of dispersive and polar components. The atoms and molecules that contribute to the surface energy / tension of a material can be explained by different types of interactions between atoms and molecules on the surface. For example, interactions caused by temporary fluctuations in the charge distribution in atoms / molecules are called dispersive interactions (e.g., van der Waals interactions) and contribute to the total surface free energy as dispersive free energy. However, polar interactions include Coulomb interactions between permanent dipoles and between permanent dipoles and induced dipoles (e.g., hydrogen bonds) and contribute to the total surface free energy as polar free energy. Therefore, the components of the surface energy / tension are composed of the addition of the dispersive energy and polar energy of the surface. Figure 5 Refers to a graphical representation of measured contact angles (in water and diiodomethane) and calculated surface free energies (total, dispersive, and polar) for silicon dioxide, silicon dioxide layers with zirconium oxynitride, and zirconium oxynitride layers encapsulated between silicon dioxide layers. Note that the date 9 / 27 / 18 refers to Figure 4The measurement date shown is 58 days after the sample creation date 8 / 1 / 18. Figure 5 The measured contact angle of the zirconium oxynitride layer grown on a single silicon dioxide layer is shown to be higher than that of the zirconium oxynitride layer encapsulated between silicon dioxide layers in water and diiodomethane. However, 58 days after the start of the experiment, the calculated surface free energy and polar free energy of the zirconium oxynitride layer encapsulated between silicon dioxide layers are higher than when the single layer of zirconium oxynitride is grown alone on silicon dioxide (i.e., non-encapsulated). Figure 5 It can be seen that the dispersion free energy does not change much over time between the zirconium oxynitride encapsulated between silicon dioxide layers and a single layer of zirconium oxynitride grown alone on silicon dioxide (i.e., non-encapsulated). Encapsulating a high refractive index zirconium oxynitride layer between low refractive index silicon dioxide layers has a large effect on the polar component of the surface free energy, which is shown in the later part of this invention.
[0054] The present invention Figure 6 and Figure 7 The high refractive index titanium dioxide layer and titanium oxynitride layer ( Figure 6 ) and high refractive index zirconium dioxide layer and zirconium oxynitride layer ( Figure 7 ) Comparison of deionized water contact angles measured over a period of time. In this comparison experiment, a normal distinct alternating 5 / 7 layer stack with high index zirconium dioxide layers and low index silicon dioxide layers was used as a baseline. Figure 6 It is shown that the measured contact angle of deionized water for the titanium dioxide layer stack is much higher than the measured contact angle of deionized water for the titanium oxynitride layer stack 10 days, 20 days and more than 35 days after the start of the experiment. Figure 7 It is shown that the measured contact angle of deionized water for the zirconium dioxide layer stack is much higher than the measured contact angle of deionized water for the zirconium oxynitride layer stack 5 and 10 days after the start of the experiment.
[0055] Referring to the present invention Figure 8 and Fig. 9 , these figures show the high refractive index titanium dioxide layer and titanium oxynitride layer ( Figure 8 ) and high refractive index zirconium dioxide layer and zirconium oxynitride layer ( Fig. 9 ) Comparison between diiodomethane contact angles measured over time. In this comparison experiment, a normal distinct 5 / 7 layer stack of a high index zirconium dioxide layer and a low index silicon dioxide layer was used as a baseline. Figure 8 It is shown that the measured contact angle of diiodomethane for the titanium dioxide layer stack is much higher than the measured contact angle of diiodomethane for the titanium oxynitride layer stack 10, 20 and 30 days after the start of the experiment. Fig. 9 It is shown that the measured contact angle of diiodomethane for the zirconium dioxide layer stack is much higher than the measured contact angle of diiodomethane for the zirconium oxynitride layer stack 5 and 10 days after the start of the experiment.
[0056] Then, Figure 6-9 The contact angle measurements shown were used to determine the total surface free energy (SFE) and the following Figure 10-15 Dispersive and polar components of surface energy for the surface in the experiments shown.
[0057] The present invention Fig.10 and Fig.11 A stack of high refractive index layers including titanium dioxide and titanium oxynitride is shown ( Fig.10 ) and a stack of high refractive index layers including zirconium dioxide and zirconium oxynitride ( Fig.11 )Comparison experiment of the total surface free energy (SFE) measured over a period of time. Fig.10 It is shown that the total surface free energy (SFE) of the titanium oxynitride layer stack measured is much higher than the total surface free energy (SFE) of the titanium dioxide layer stack measured 5, 10, 20 and nearly 40 days after the start of the experiment. Fig.11 It is shown that the total surface free energy (SFE) of the zirconium oxynitride layer stack measured 5 and 10 days after the start of the experiment is much higher than the total surface free energy (SFE) of the titanium dioxide layer stack measured. In some embodiments, the total surface energy of the resulting metal (Ti / Zr) oxynitride-based anti-reflection structure is between about 50-70 mN / m.
[0058] The present invention Fig.12 and 13 shows that in a stack of high refractive index layers including titanium dioxide and titanium oxynitride ( Fig.12 ) and a stack of high refractive index layers including zirconium dioxide and zirconium oxynitride ( Fig.13 ) over a period of time. Fig.12 It shows that the measured dispersion component surface energy between the titanium dioxide layer and the titanium oxynitride layer merged to about 40 mN / m nearly 40 days after the start of the experiment. Fig.13 It is shown that there is not much difference in the dispersion component surface energy measured between the zirconium dioxide layer and the zirconium oxynitride layer 5 and 10 days after the start of the experiment. Fig.12 and 13 These experiments shown illustrate that the dispersive component of the surface energy does not affect or vary much over time between a stack of titanium dioxide layers and titanium oxynitride layers or a stack of zirconium dioxide layers and zirconium oxynitride layers. From this experiment it can be concluded that the dispersive interactions (e.g., van der Waals interactions) between atoms and molecules caused by temporary fluctuations in charge distribution differ very little between metal oxide and metal oxynitride layers, where the metals are at least from, but not limited to, titanium and zirconium.
[0059] The present invention Fig.14 and 15The high refractive index layers of titanium dioxide and titanium oxynitride ( Fig.14 ) and high refractive index layers of zirconium dioxide and zirconium oxynitride ( Fig.15 ) over a period of time. Fig.14 It shows that 5 days, 10 days, 20 days and nearly 40 days after the start of the experiment, the measured polar component surface energy of titanium oxynitride is much higher than the measured polar component surface energy of titanium dioxide. Fig.15 It is shown that the polar component surface energy of zirconium oxynitride measured 5 and 10 days after the start of the experiment is much higher than the polar component surface energy of zirconium dioxide measured. From this experiment, it can be concluded that the polar interactions (such as hydrogen bonds) between permanent dipoles and between permanent dipoles and induced dipoles are much higher for zirconium oxide layers than for zirconium dioxide layers.
[0060] Fig.14 and Fig.15 It is shown that for coatings using only high-index metal (Ti / Zr) oxides, the polar energy decreases over time and approaches zero, which tends to result in a decrease in hydrophilic properties. In contrast, metal (Ti / Zr) oxynitrides show that the polar surface energy decreases initially and then stabilizes at a higher non-zero value, which helps maintain a more stable hydrophilic property. In some embodiments, the polar energy of the metal (Ti / Zr) oxynitride is between about 15-40 mN / m. According to some embodiments of the present invention, the stability of the polar component energy of the metal (Ti / Zr) oxynitride may depend on the optimal nitrogen content used when preparing the metal (Ti / Zr) oxynitride film. If nitrogen exceeding this content is used during the sputtering process, the hydrophilic properties of the metal (Ti / Zr) oxynitride film may be unstable, and a controllable total surface energy of the metal (Ti / Zr) oxynitride film in the range of about 50-70 mN / m may not be obtained.
[0061] It should be noted that the presence of a SiO2 layer alone in the optical stack will impart a hydrophilic-like property to the anti-reflective optical stack for a short period of time, which will then diminish over time. Figure 6-15 The description shows that high-refractive-index metal oxynitride coatings embedded between SiO2 layers have a permanent effect on the hydrophilic behavior of the anti-reflective optical stack. When high-refractive-index metal oxynitrides are encapsulated between SiO2 layers, the combined layers work synergistically. Figure 6-15 In all anti-reflection optical stacks described in , the top layer always remains SiO2. Figure 10-15 The surface energy data show that the use of oxynitride coatings leads to an increase in the surface energy of the entire anti-reflective optical stack.
[0062] Now refer to the present invention Fig.16, which shows a cleanability test, which is used to determine how easily oily residues are removed from the surface of a lens. At the beginning of the experiment, a synthetic skin oil (sebum) was applied using a tampo rubber stamp. A controlled amount of sebum needs to be applied using a tampo stamp to provide a predictable amount of optical haze. The temperature of the sebum was controlled at 60°C. Lenses with a base curve of 4 or 6 diopters were used. Limiting the curve range improves the repeatability of the test. The optical haze of the sample was then measured three times after the lens was rotated 120 degrees. The average of these measurements is the reported initial haze. The sample was placed in a friction test system with a 2.2 kg weight on a soft pad with a polyester cloth, the weave of which passed through the sample at a 90° angle to rub (stroke). After 6 rubs, the cloth was changed and the haze was measured. At the end of 18 rubs, the final haze was measured. In some embodiments of the present invention, using an anti-fogging agent, the punch rate of sebum should be about 35% transmission. This is because some surfaces have some different textures. Heating the sebum and the stamping pressure contribute to the uniformity and repeatability of the haze starting point. As mentioned above, at each haze measurement, the sample is rotated approximately 120 degrees and the average is taken. In hydrophobic samples, the haze measurement can sometimes be worst due to the smearing of sebum. This is one of the main drawbacks of hydrophobic coatings, where oils and stains tend to migrate on the surface due to the low surface energy.
[0063] From the haze readings after the initial press and after 18 rubs with the polyester cloth, the cleanability ratio can be calculated by subtracting the final haze reading after 18 rubs from the haze reading at the initial press, dividing the result by the haze reading at the initial press, and multiplying by 100, which is represented by the mathematical formula of "cleanability ratio", i.e., = (initial reading - final reading) / initial reading * 100.
[0064] The above formula is used to compare the "cleanability ratio" of lenses of different materials, manufacturers and manufacturing processes. Fig.16 Shown is a comparison of the "cleanability ratio" of zirconium oxynitride and zirconium dioxide used as a high index layer of an anti-reflection structure. Fig.16 It was further shown that the initial haze reading of the anti-reflection structure stack prepared using zirconium dioxide as the high refractive index layer was 33.88, and the initial haze reading of the anti-reflection structure stack prepared using zirconium oxynitride as the high refractive index layer was 37.88. After rubbing 18 times with polyester cloth, the haze reading of the anti-reflection structure stack prepared using zirconium dioxide as the high refractive index layer was 23.58, and the haze reading of the anti-reflection structure stack prepared using zirconium oxynitride as the high refractive index layer was 0.87. The "cleanability ratio" was calculated using the above formula, Fig.16It is shown that the "cleanability ratio" of the anti-reflection structure stack prepared using the high-index zirconium oxynitride layer is much higher (97.63) than the "cleanability ratio" of the anti-reflection structure stack prepared using the high-index zirconium dioxide layer.
[0065] Fig.17 A comparison of the cleanability ratios between a competitor's hydrophobic coating, an easy-to-clean coating from applicant's earlier U.S. Patent Publication No. 2015 / 0226886 (the contents of which are incorporated herein by reference), and the coating disclosed in the present invention (labeled as hydrophilic AR) is shown. Fig.17 It can be concluded that the surfaces provided by the applicant's earlier US Patent Publication No. 2015 / 0226886 and the easy-to-clean coating of the present invention (labeled as hydrophilic AR) are better than Fig.17 The industry standard hydrophobic coatings shown in Comparative Examples 1-6 are more effective at cleaning by wiping. For example, the cleanability ratios of the industry standard hydrophobic coatings shown in Comparative Examples 1-6 are between 17% and 70%. The cleanability ratios of Applicant's application U.S. Patent Application No. 2015 / 0226886 and the present invention are 92% and 95%, respectively. Therefore, the lenses according to the present invention show greater cleanability than the "easy-to-clean" lenses currently tested on the market.
[0066] Although the present invention has been described from the perspective of specific embodiments and applications, those skilled in the art can, based on this teaching, produce other embodiments and modifications without departing from the spirit of the claimed invention or exceeding its scope. Therefore, it should be understood that the drawings and descriptions herein are provided as examples to facilitate understanding of the present invention and should not be interpreted as limiting its scope.
Claims
1. An ophthalmic product having easy-to-clean and anti-reflective properties, comprising: a substrate having a surface; and, a stack on said surface; The stack comprises a plurality of alternating low refractive index layers and high refractive index layers, the low refractive index layers comprising metal oxides, the high refractive index layers comprising 1) at least one metal oxynitride layer, or 2) at least one metal oxynitride layer and at least one metal oxide layer; Wherein the high refractive index metal oxynitride layer comprises a titanium oxynitride layer or a zirconium oxynitride layer and is encapsulated between two low refractive index metal oxide layers, the ophthalmic article comprises a surface free energy in the range of 50-70 mN / m over a long term.
2. The ophthalmic article of claim 1, wherein the low refractive index metal oxide comprises silicon dioxide.
3. The ophthalmic article of claim 1, wherein the high refractive index metal oxide comprises titanium dioxide or zirconium dioxide.
4. The ophthalmic article of claim 1, wherein the ophthalmic article comprises a polar surface energy in the range of 15-40 mN / m over a long term.
5. The ophthalmic article of claim 1, wherein the surface cleanability ratio of the ophthalmic article is greater than 90%.
6. The ophthalmic article of claim 5, wherein a high refractive index metal oxynitride layer comprising zirconium oxynitride is encapsulated between two of the low refractive index metal oxide layers comprising silicon dioxide, the ophthalmic article having a surface cleanability ratio of 97.63%.
7. An optical stack imparting easy-cleaning and anti-reflection properties on a surface, comprising: a high refractive index metal oxynitride layer comprising a titanium oxynitride layer or a zirconium oxynitride layer encapsulated between two low refractive index metal oxide layers; The surface free energy of the optical stack was maintained in the range of 50-70 mN / m over a period of 40 days.
8. The optical stack of claim 7, wherein the low refractive index metal oxide layer comprises silicon dioxide.
9. The optical stack of claim 7, wherein the optical stack further comprises a high refractive index metal oxide layer comprising titanium dioxide or zirconium dioxide.
10. The optical stack of claim 7, wherein the optical stack comprises a polar surface energy at 40 days in the range of 15-40 mN / m.
11. The optical stack of claim 9, wherein the high refractive index layer of the metal oxynitride and the high refractive index layer of the metal oxide corresponding to the metal oxynitride have approximately the same refractive index. 12 . The optical stack of claim 9 , wherein a surface roughness of a high refractive index layer of a metal oxynitride is higher than a surface roughness of a high refractive index layer of a metal oxide corresponding to the metal oxynitride.
13. A method of making an ophthalmic article having easy-to-clean and anti-reflective properties, comprising: providing a substrate having a surface; as well as forming a stack on the surface; The stack comprises a plurality of alternating low refractive index metal oxide layers and high refractive index layers, the high refractive index layers comprising 1) at least one metal oxynitride layer, or 2) at least one metal oxynitride layer and at least one metal oxide layer, and encapsulating a high refractive index metal oxynitride layer comprising a titanium oxynitride layer or a zirconium oxynitride layer between two low refractive index metal oxide layers; The ophthalmic article has a surface cleanability ratio of greater than 90%.
14. A method according to claim 13, wherein alternating layers of low refractive index silicon dioxide and high refractive index titanium dioxide or zirconium dioxide and high refractive index titanium oxynitride or zirconium oxynitride are coated on the surface.
15. The method according to claim 13, wherein a titanium oxynitride layer or a zirconium oxynitride layer with a high refractive index is encapsulated between two silicon dioxide layers with a low refractive index.
Citation Information
Patent Citations
Easy-clean coating
US10613255B2
Electrochromic device having a self-cleaning hydrophilic coating
US20030048538A1
Communication apparatus, relay apparatus and communication method
US20140074912A1
Easy-Clean Coating
US20150226886A1
Anti-fog element
US5854708A